Patient vs provider perspectives of 30-day hospital readmissions - Lisa Shieh; Andrea Smeraglio; Paul A Heidenreich; Gomathi Krishnan; Joseph Hopkins; Jonathan Chen (BMJ Open Quality)
Objective To compare patients’ and providers’ views on contributors to 30-day hospital readmissions.Design Analysis of a qualitative interview survey between 18 May–30 June 2015.Setting Interviews were conducted during the 30-day readmission hospitalisation at a single tertiary care academic hospital.Participants We conducted 178 interviews of readmitted patients.Measures We queried opinions of what factors patients believed contributed to their rehospitalisation and compared this with the perspective of the index admission provider. The primary outcome was the view that the readmission was preventable. A review by a RN (nurse) case manager also provided an assessment based on patient report, provider report and chart review.Results Patients were more likely to view a readmission as preventable compared with physicians (p<0.0001). Patients identified system issues (defined as factors controlled by the hospital discharge process) as contributors to their readmission in 58% (103/178) of cases while providers identified system issues as the contributor to a patients’ readmission in 2% (2/101) of cases. Patients with poor functional status were more likely to feel the cause of their readmission was due to system issues than patients with better functional status (p=0.03). A RN case manager review determined that in 48% (86/178) of cases the system had some amount of contribution to a patient’s readmission. There was no significant difference in belief that the readmission was preventable between the RN case manager and the patient (p=0.47).Conclusions Readmitted patients often feel that the hospital system contributed to their readmission. Providers did not recognise patient and RN case manager identified issues as contributors to hospital readmissions.